Systematic comparison of hydrogen production from fossil fuels and biomass resources - Peng, Kang; Morrow, Gary; Xiaolei, Zhang; Tipeng, Wang; Tan, Zhongfu; Agarwal, Jayant (International Journal of Agricultural and Biological Engineering, 2017)
Fossil fuels are the main energy source to satisfy the worldwide energy demands. However, the energy demands are increasing and the supply of fossil fuels is decreasing, thus many countries are looking for other fuel sources. Differing from the traditional fuels, hydrogen is considered as one of the most promising energy sources due to its intrinsic features such as clean, efficient, safe and sustainable. Developing novel technologies for hydrogen production from renewable sources (such as biomass) becomes a core area for the investigation of hydrogen industry. Within this work, different pathways for hydrogen production including steam reforming, electrolysis, and biomass gasification have been systematically compared in terms of yield and cost. This comparison is unique since the systematic evaluation was conducted from many aspects for all the hydrogen production pathways, especially those by involving the biomass gasification that still lack of available literatures. The assessment methods involved energy analysis, exergy analysis and economic analysis. It was concluded that steam reforming remains the cheapest method of hydrogen production at 1.748 /kg, however, steam reforming is not an ideal process currently or for the future, gasification and electrolysis remains competitive with high yield but requires relatively high initial and annual expenditure. For biomass gasification, though its energy efficiency is lower than steam reforming, it has relatively higher mass yield, demonstrating the feasibility of this process for hydrogen production. Further for biomass gasification, the selection of correct feedstock is a key to maximize its yield, i.e. a yield of 82.47% is possible with corn stover fed gasification. Keywords: hydrogen production, biomass feedstock, gasification, pyrolysis, fossil fuel, techno-economic assessment, exergy DOI: 10.25165/j.ijabe.20171006.2990 Citation: Kang P, Morrow G, Zhang X L, Wang T P, Tan Z F, Agarwal J. Systematic comparison of hydrogen production from fossil fuels and biomass resources. Int J Agric & Biol Eng, 2017; 10(6): 192–200.